Do Drug Warnings and Market Withdrawals Have an Impact on the Number of Calls to Teratogen Information Services? - Sheehy, O.; Gendron, M.-P.; Martin, B.; Bérard, A. (Pharmacopsychiatry, 2012)
IMAGe provides information on risks and benefits of medication use during pregnancy and lactationThe aim of this study was to determine the impact of Health Canada warnings on the number of calls received at IMAGe.We analyzed calls received between January 2003 and March 2008. The impact of the following warning/withdrawal were studied: paroxetine and risk of cardiac malformations (09/29/2005), selective serotonin reuptake inhibitors (SSRIs) and risk of persistent pulmonary hypertension of the newborn (PPHN) (03/10/2006), and impact of rofecoxib market withdrawal (09/30/2004). Interrupted auto-regressive integrated moving average (ARIMA) analyses were used to test the impact of each warning on the number of calls received to IMAGe.61 505 calls were analyzed. The paroxetine warning had a temporary impact increasing the overall number of calls to IMAGe, and an abrupt permanent effect on the number of calls related to antidepressant exposures. The PPHN warning had no impact but we observed a significant increase in the number of calls following rofecoxib market withdrawal.Health Canada needs to consider the increase in the demand of information to IMAGe following warnings on the risk of medication use during pregnancy.
Keywords: antidepressants; pregnancy and lactation; drug warnings; anxiety; teratogen information services